INTRODUCING ENGLISH TO EARLY CHILDHOOD THROUGH SINGING WITH THE TOTAL PHYSICAL RESPONSE METHOD - Septi Gumiandari (Universitas Muhammadiyah Kalimantan Timur, 2021)
Introducing English from an early age should be supported by adequate media and infrastructure. Learning should be arranged in such a way as to give birth to learning activities that are important and fun. Therefore, it requires perfect and efficient teaching methods. Research on